2005
DOI: 10.1097/01.brs.0000149186.63457.20
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Distribution of Tumor Necrosis Factor Alpha in Human Lumbar Intervertebral Discs: A Study in Surgical Specimen and Autopsy Controls

Abstract: Tumor necrosis factor alpha is substantially expressed in disc material of symptomatic patients (surgical specimens) in comparison to samples taken at autopsy. The expression of tumor necrosis factor alpha in early fetal/infantile nucleus pulposus may indicate 'physiologic' tissue disarrangement with closure of the blood vessel canals. The expression of tumor necrosis factor alpha in adult discs, in contrast, is statistically associated with disc degeneration. Its occurrence in adults of more advanced age sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
254
1
9

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 299 publications
(273 citation statements)
references
References 60 publications
9
254
1
9
Order By: Relevance
“…Furthermore, the patients with lumbar radiculopathy caused by disk herniation were younger than those with cervical myelopathy. A previous cadaveric study demonstrated that the correlation between anular TNF-a and age was highly significant [29]. Therefore, there is a possibility that the differences in cytokines among the three groups were attributable to age.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, the patients with lumbar radiculopathy caused by disk herniation were younger than those with cervical myelopathy. A previous cadaveric study demonstrated that the correlation between anular TNF-a and age was highly significant [29]. Therefore, there is a possibility that the differences in cytokines among the three groups were attributable to age.…”
Section: Discussionmentioning
confidence: 91%
“…In herniated disc, TNF-a is expressed at higher levels compared to asymptomatic or autopic controls [29]. Moreover, cytokines play a role in the generation of neuropathic pain both in the peripheral and central nervous systems [30][31][32] and participation of pro-inflammatory cytokines in the genesis of changes of nervous tissue and symptoms generated by lumbar disc herniation has been emphasized by several authors [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…The local production of matrix-degrading enzymes is a key event leading to degeneration, but it must be also considered in the context of the upstream molecules, such as cytokines, which regulate enzyme synthesis. IVD cells have a capacity to express a range of cytokines [6,7], including pro-inflammatory molecules, such as both isoforms of interleukin-1, alpha (IL-1a) and beta (IL-1b) [8] and tumor necrosis factor alpha (TNF-a) [9]. It has been proposed that IL-1 can regulate IVD cell expression of key matrixdegrading enzymes in vitro [10] and in vivo [11], placing this cytokine as a main factor inducing degeneration.…”
Section: Introductionmentioning
confidence: 99%